Tính nhanh tổng sau: A = 1+2+22+23+....+249
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a, A = 1 + 3 + 32 + 33 + ... + 32000
3.A = 3 + 32 + 33+ 33+... + 32001
3A - A = 3 + 32 + 33 + ... + 32001 - (1 + 3 + 32 + 33 + ... + 32000)
2A = 3 + 32 + 33 + ... + 32001 - 1 - 3 - 32 - 33 - ... - 32000
2A = 32001 - 1
A = \(\dfrac{3^{2001}-1}{2}\)
a: \(=\left(1+2\right)+2^2\left(1+2\right)+...+2^{48}\left(1+2\right)\)
\(=3\left(1+2^2+...+2^{48}\right)⋮3\)
b: \(2^0+2^1+2^2+...+2^{101}\)
\(=\left(1+2+2^2\right)+...+2^{99}\left(1+2+2^2\right)\)
\(=7\left(1+...+2^{99}\right)⋮7\)
c: 2A=2+2^2+...+2^101
=>A=2^101-1
a) \(S=1+2+2^2+2^3+...+2^{2022}=\dfrac{2^{2022+1}-1}{2-1}=2^{2023}-1\)
b) \(S=1+4+4^2+4^3+...+4^{2022}=\dfrac{4^{2022+1}-1}{4-1}=\dfrac{4^{2023}-1}{3}\)
\(S=1+2+2^2+2^3+...+2^{2022}\\ 2S=2+2^2+2^3+2^4+...+2^{2023}\\ 2S-S=2+2^2+2^3+2^4+...+2^{2023}-1-2-2^2-2^3-...-2^{2022}\\ S=2^{2023}-1\\ S=4+4^2+4^3+...+4^{2022}\\ 4S=4^2+4^3+4^4+...+4^{2023}\\ 4S-S=4^2+4^3+4^4+...+4^{2023}-4-4^2-4^3-...-4^{2023}\\ 3S=4^{2023}-4\\ S=\dfrac{4^{2023}-4}{3}\)
a) \(A=2+2^2+2^3+...+2^{2017}\)
\(2A=2^2+2^3+2^4+...+2^{2018}\)
\(2A-A=\left(2^2+2^3+2^4+...+2^{2018}\right)-\left(2+2^2+2^3+...+2^{2017}\right)\)
\(A=2^{2018}-2\)
b) \(C=1+3^2+3^4+...+3^{2018}\)
\(3^2\cdot C=3^2+3^4+3^6+...+3^{2020}\)
\(9C-C=\left(3^2+3^4+3^6+...+3^{2020}\right)-\left(1+3^2+3^4+...+3^{2018}\right)\)
\(8C=3^{2020}-1\)
\(\Rightarrow C=\dfrac{3^{2020}-1}{8}\)
\(Toru\)
\(A=2+2^2+...+2^{20}\)
\(2A=2^2+2^3+...+2^{21}\)
\(2A-A=2^2+2^3+...+2^{21}-2-2^2-...-2^{20}\)
\(A=2^{21}-2\)
___________
\(B=5+5^2+...+5^{50}\)
\(5B=5^2+5^3+...+5^{51}\)
\(5B-B=5^2+5^3+...+5^{51}-5-5^2-...-5^{50}\)
\(4B=5^{51}-5\)
\(B=\dfrac{5^{51}-5}{4}\)
___________
\(C=1+3+3^2+...+3^{100}\)
\(3C=3+3^2+...+3^{101}\)
\(3C-C=3+3^2+...+3^{101}-1-3-3^2-...-3^{100}\)
\(2C=3^{101}-1\)
\(C=\dfrac{3^{101}-1}{2}\)
Lời giải:
$E=1-2+22-23+24-25+.....+21000$
$=(1-2)+(22-23)+(24-25)+......+(20998-20999)+21000$
$=(-1)+(-1)+(-1)+....+(-1)+21000$
Số lần xuất hiện của -1: $[(20999-22):1+1]:2+1=10490$
$E=(-1).10490+21000=10510$
Ta có:
A = 2 + 22 + 23 + … + 22017
2A = 2.( 2 + 22 + 23 + … + 22017)
2A = 22 + 23 + 24 + … + 22018
2A – A = (22 + 23 + 24 + … + 22018) – (2 + 22 + 23 + … + 22017)
Vậy A = 22018 – 2
Ta có: A = 2 + 22 + 23 + … + 22017
2A = 2.( 2 + 22 + 23 + … + 22017)
2A = 22 + 23 + 24 + … + 22018
2A – A = (22 + 23 + 24 + … + 22018) – (2 + 22 + 23 + … + 22017)
A = 22018 – 2
Vậy A = 22018 – 2
A = 1+2+22+23+....+249
2A = 2 ( 1+2+22+23+....+249) =2+22+23+....+250
=> 2A - A = A = 250-1
Vậy A = 250-1
A = 1+2+22+23+....+249
2A = 2 ( 1+2+22+23+....+249) =2+22+23+....+250
=> 2A - A = A = 250-1
Vậy A = 250-1